AN ONTOLOGICAL FRAMEWORK FOR REQUIREMENT CHANGE MANAGEMENT IN DISTRIBUTED ENVIRONMENT - Khatoon, A.; Hafeez, Y.; Asghar, S.; Ali, T. (The Nucleus, 2014)
Global Software Development (GSD) is getting fame in the software industry gradually. However, in GSD, multiple and diverse stakeholders are involved in the development of complex software systems. GSD introduces several challenges, i.e. physical distance, time zone, culture difference, language barriers. As requirements play a significant role in any software development. The greatest challenge in GSD environment is to maintain a consistent view of the system even if the requirements change. But at the same time single change in the requirement might affect several other modules. In GSD different people use terms and have different ways of expressing the concepts for which people at remote sites are unable to get uniformity regarding the semantics of the terms. In a global environment requires effective communication and coordination. However, to overcome inconsistencies and ambiguities among the team members and to make the team members aware of the consistent view, a shared and common understanding is required. In this paper an approach beneficial to software industry has been proposed, focusing on changing requirements in a Global Software Development environment. A case study has been used for the evaluation of the proposed approach. Therefore, Requirements change management process has been improved by applying the approach of the case study. The proposed approach is beneficial to the software development organizations where frequent changes occur. It guided the software industry to provide the common understandings to all the development teams residing in remote locations.